Mechanical Properties of Polypropylene/Epoxidized Natural Rubber Blend via Mixing Ratio Analysis - M.Y, YUHAZRI; F.R, FAISAL; N.Z, SHARAFINA; A.M, HAIRUL EFFENDY; A.R, TOIBAH; S.T, RAHMAH; M.A, ASYADI AZAM; M, NORAIHAM (2012)
REFER TO FILE